Rapid and sensitive detection of lower respiratory tract infections by stuffer‐free multiplex ligation‐dependent probe amplification. Issue 4 (5th December 2013) - Chung, Boram; Shin, Gi Won; Park, Chan Kwon; Choi, Woong; Chung, Yeun‐Jun; Yoon, Hyung Kyu; Jung, Gyoo Yeol
<x xml:space="preserve">Abstract</x> Lower respiratory tract infection is one of the most common infectious diseases. However, conventional methods for detecting infectious pathogens are time‐consuming, and generally have a limited impact on early therapeutic decisions. We previously reported a rapid and sensitive method for detecting such pathogens using stuffer‐free multiplex ligation‐dependent probe amplification coupled with high‐resolution CE‐SSCP. In this study, we report an application of this method to the detection of respiratory pathogens. As originally configured, this method was capable of simultaneously detecting seven bacterial species responsible for lower respiratory tract infections, but its detection limit and assay time were insufficient to provide useful information for early therapeutic decisions. To improve sensitivity and shorten assay time, we added a target‐specific preamplification step, improving the detection limit from 50 pg of genomic DNA to 500 fg. We further decreased time requirements by optimizing the hybridization step, enabling the entire assay to be completed within 7 h while maintaining the same detection limit. Taken together, these improvements enable the rapid detection of infectious doses of pathogens (i.e. a few dozen cells), establishing the strong potential of the refined method, particularly for aiding early treatment decisions.